Fresno's Human Services Coalition Luncheon Honoring Karen Humphrey - Watkins, Howard::::::::: (1985)
Karen Humphrey thanking Joan Mihay; seated: Dianne Spaulding, Supervisor Judy Andreen, Fresno County Economic Opportunities Commission Director Joe Williams, Councilmember Les Kimber, City Clerk Jackie Ryle